Economic Analysis on the Market Participation Decision of Fishermen in Jaffna District, Sri Lanka - Umashankar, K.; Prasath, S. (Sri Lanka Agricultural Economics Association, 2011)
This research attempts to identify the socio economic and geographical characteristics that have been imposing constraints on the market participation decision of the fishermen in the Jaffna district, Sri Lanka. Purposive sampling method was used to select 278 respondents. Collected data were compiled and analyzed using multinomial logit model by using the statistical software STATA 10. The results revealed that the harvesting per month and access to the market information are significant at 10%, and 1% levels respectively and increased the local market participation through the middleman by 0.14, 17.36 respectively. The investment for the future manifests a significant negative impact at 10% level and decreases the local market participation rate by 1.83. Knowing the market price and termination of business relations with the buyer are found to be significant at 10%, and 5% respectively and increases the participation rate in the southern market through middleman by 0.82, 1.60 respectively. The research concludes that the market intelligence of the local fishing population can be upgraded by conveying the market related information via local Media. This may help the fishermen to make a rational decision regarding the marking of their catch and may also help in bypassing the middlemen. Formal credit may help the fishermen to invest in the future and that may in turn motivate them to participate in the southern market rather than in the local market. To avoid the fungiblity of credit, the credit providing agencies may sanction the credit in kind. In view of safeguarding the local consumers, fishermen's local market participation rate could be encouraged by organizing contract arrangements with the wholesalers in the local market.
Keywords: Fish marketing; Multinomial logit; Market participation decision